1999
DOI: 10.1021/ie980793m
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tray Geometry on Scaling Up Distillation Efficiency from Laboratory Data

Abstract: This paper studies the effect of tray geometry (especially hole diameter) and liquid tray composition on tray efficiency in a bench-scale distillation column. The results of this study are used for scaling up tray efficiency. Two binary systems, ethanol/water and cyclohexane/n-heptane, were considered. The operating conditions were atmospheric pressure and total reflux. For each one, two different hole diameters (small and large) were also tested. Kirschbaum's industrial data (1962) for the ethanol/water syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Typical experimental setups used for conducting these experiments include small cross-flow trays as well as Oldershaw columns (e.g., Manivannan et al), in which the liquid on the tray is considered as perfectly mixed, and hence, E OG = E MV . However, this approach does not account for wall effects that are hardly negligible on the small scale and lacks agreed criteria that allow reproducing the large-scale froth condition on a small scale. , The proposed criteria include the fractional approach to flooding, the clear liquid height, and the tray geometry . Other examples of small-scale studies and relevant criteria are covered by Finch and Van Winkle, Garrett et al, and Biddulph et al…”
Section: Revisiting the Efficiency Conceptsmentioning
confidence: 99%
See 2 more Smart Citations
“…Typical experimental setups used for conducting these experiments include small cross-flow trays as well as Oldershaw columns (e.g., Manivannan et al), in which the liquid on the tray is considered as perfectly mixed, and hence, E OG = E MV . However, this approach does not account for wall effects that are hardly negligible on the small scale and lacks agreed criteria that allow reproducing the large-scale froth condition on a small scale. , The proposed criteria include the fractional approach to flooding, the clear liquid height, and the tray geometry . Other examples of small-scale studies and relevant criteria are covered by Finch and Van Winkle, Garrett et al, and Biddulph et al…”
Section: Revisiting the Efficiency Conceptsmentioning
confidence: 99%
“…However, this approach does not account for wall effects that are hardly negligible at small-scale and lacks agreed criteria that allow reproducing the large-scale froth condition on a small-scale [33][34] . Proposed criteria include the fractional approach to flooding 35 , the clear liquid height and the tray geometry 36 . Other examples of small-scale studies and relevant criteria are covered by Finch and Van Winkle 37 , Garrett et al 38 and Biddulph et al 39 .…”
Section: Point Efficiencyunclassified
See 1 more Smart Citation
“…The primary prerequisite in modeling the neural networks is the availability of a database. Therefore, the experimental data from the following references have been utilized in this work, respectively: Lopez and Kirschbaum (Lopez andCastells, 1999 andKirschbaum, 1962), Proctor (Proctor et al, 1998), Kastanek and Biddulph (Kastanek and Standart, 1967;Biddulph and Dribika, 1986), Rush and Jones (Rush and Stirba, 1957;Jones and Pyle, 1995), Kunesh (Kunesh et al, 1996), Rush (Rush and Stirba, 1957) and Lopez and Yanagi (Kunesh et al, 1996;Yanagi and Sakata, 1982). The physical properties, operating conditions and specifications of the tray geometry are exhibited in Table 1.…”
Section: Model Input Parameters and Training For The Neural Networkmentioning
confidence: 99%
“…Colwell [11] and Bennett et al [12] obtained the expressions of gas holdup related to the tray geometry and fluid velocity based on experiments, respectively. Solari and Bell [13] used fluorescence technology to measure the detailed residence time and velocity distribution of five sieve trays with a diameter of 1.22 m. L opez and Castells [14] experimentally analyzed the effect of tray geometry (especially hole diameter) and liquid tray composition on tray efficiency in a bench-scale distillation column. The research findings revealed that trays with smaller hole diameters exhibited higher efficiencies compared to those with larger hole diameters.…”
Section: Introductionmentioning
confidence: 99%